2015
DOI: 10.1097/ypg.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Active ribosomal genes, translational homeostasis and oxidative stress in the pathogenesis of schizophrenia and autism

Abstract: Our findings confirm the hypothesis of disturbance of the 'translational homeostasis' in the pathogeneses of autism and schizophrenia, and would help explain why oxidative stress markers are discovered in most autism studies, whereas similar reports related to schizophrenia are far less consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
2
14
0
1
Order By: Relevance
“…For instance, insulin release that is stimulated by glucose production in β-cells has been linked to H 2 O 2 regulatory action [ 57 ]. Recent mathematical modeling described the OS dynamics to be of oscillatory nature [ 58 ] and tissue depending [ 59 ], which may explain the inconsistency of experimental data related to antioxidant enzymes measurements. Alternatively, focusing on stable OS markers such as MDA may reflect more reliable information on OS damage under long-term dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, insulin release that is stimulated by glucose production in β-cells has been linked to H 2 O 2 regulatory action [ 57 ]. Recent mathematical modeling described the OS dynamics to be of oscillatory nature [ 58 ] and tissue depending [ 59 ], which may explain the inconsistency of experimental data related to antioxidant enzymes measurements. Alternatively, focusing on stable OS markers such as MDA may reflect more reliable information on OS damage under long-term dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…ALS (amyotrophic lateral sclerosis), schizophrenia, mitochondrial disorders, hypertension and diabetes [1][2][3][4][5][6][7][8][9][10][11][12][13]. Dickens et al [14] reported that MD in vitro enhances intracellular ROS production leading to endogenous OS in endothelial cells, and Garcia et al [15] showed that Mg 2+ supplementation reduces ROS formation in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Given that high oxidation activity must be balanced with antioxidant activity in the brain, it is an organ prone to oxidation-related damage [ 6 , 7 , 8 ]. Such OS is a potential factor in brain deterioration and loss of gray matter, which lead to issues with cognition and daily functioning [ 9 , 10 , 11 , 12 ]; furthermore, OS has been associated with a plethora of psychiatric disorders [ 13 , 14 , 15 , 16 , 17 ]. One such disorder, schizophrenia is characterized by emotional, cognitive, and behavioral disturbances, as well as inaccurate perceptions of reality and high mortality and morbidity [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%